2013
DOI: 10.1007/s00221-013-3500-x
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of shifts of spatial attention induced by object words with spatial associations: an ERP study

Abstract: The present study used event-related potentials (ERPs) to explore the nature of shifts of spatial attention induced by object words with spatial associations. Specifically, we presented participants with cue words that denote objects that typically appear in high or low places (e.g., "moon," "mouse") at the center of the screen. After the presentation of the cue words, participants were asked to identify a target letter ("p" or "q") at the top or bottom of the screen. Although the cues did not predict target l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…and "snake" closely resemble actual perceptions in the upper and lower visual fields, respectively (Quadflieg et al, 2011; see also Zhang et al, 2013). Although such attentional orienting is well documented, notice that it should facilitate perception at the implied location, not hinder it (Hommel, Pratt, Colzato, & Godijn, 2001).…”
Section: Location-specific Perceptual Representationmentioning
confidence: 79%
See 2 more Smart Citations
“…and "snake" closely resemble actual perceptions in the upper and lower visual fields, respectively (Quadflieg et al, 2011; see also Zhang et al, 2013). Although such attentional orienting is well documented, notice that it should facilitate perception at the implied location, not hinder it (Hommel, Pratt, Colzato, & Godijn, 2001).…”
Section: Location-specific Perceptual Representationmentioning
confidence: 79%
“…or downward (e.g., "cellar") spatial associations (e.g., Bergen et al, 2007;Chasteen, Burdzy, & Pratt, 2010;Duschig et al, 2012Duschig et al, , 2013Estes et al, 2008;Goodhew et al, 2014;Gozli et al, 2013;Quadflieg et al, 2011;Richardson et al, 2003;Verges & Duffy, 2009;Zhang et al, 2013), maps clearly onto the perceptual matching account described in the introduction: The visual target was described as appearing in either the "matching" location or a "mismatching" location. Thus, our theoretical conceptualization treated the congruence between the spatial association of the cue and the physical location of the target as a categorical factor.…”
Section: A Categorical Model Of Spatial Codingmentioning
confidence: 82%
See 1 more Smart Citation
“…The attenuated N400s observed are interpreted as a possible contribution of semantics (Feldman et al, 2009; Kielar and Joanisse, 2011). The other ERP component would be N100, reflecting attention allocation, working memory operation (Zhang et al, 2013), early perceptual processes such as feature integration and encoding, feature-mapping processes of speech sounds, the automatic lexical classification of a word and is relatively independent of the task (Spironelli and Angrilli, 2009) and a transitional processing stage between auditory and abstract phonological representations. So it is termed as “recognition potential.” The shorter latency of N100 usually represents higher mental ability.…”
Section: Introductionmentioning
confidence: 99%
“…A key (and, at first sight, puzzling) feature of the available literature is that words with up/down associations can both interfere with (Bergen, Lindsay, Matlock, & Narayanan, 2007; Dudschig, Lachmair, de la Vega, De Filippis, & Kaup, 2012; Estes et al, 2008; Gozli, Chasteen, & Pratt, 2013; Verges & Duffy, 2009), or facilitate the discrimination of (Chasteen, Burdzy, & Pratt, 2010; Gozli et al, 2013; Zhang et al, 2013), visual targets in congruent locations. Gozli and colleagues (2013) scrutinized this pattern of findings and showed that interference in compatible location occurs only when SOA is short (<400 ms), whereas facilitation is observed at longer SOAs.…”
mentioning
confidence: 99%